Neurologic fecal incontinence - Wyndaele J. (2017)
Introduction: This manuscript summarizes the work of Committee 10 on neurologic bladder and bowel of the International Consultation on Incontinence in 2008-2009. As the data are very large the outcome is presented in different manuscripts. This manuscript deals with neurologic fecal incontinence (FI). Methods: Through in debt literature review all aspects of neurologic urinary and FI were studied for levels of evidence. Recommendations for diagnosis and treatment, and for future research were made. Results: Pathophysiology was summarized for different levels of lesions. For epidemiology, specific diagnostics, conservative treatment, and surgical treatment of neurologic FI levels of evidence and grades of recommendation were made. Conclusions: Though data are available that advice and guide in the management of FI in neurologic patients, not many data are with a high level of evidence or high grade of recommendation. More and well-structured research is needed. © 2009 Wiley-Liss, Inc.